2014
DOI: 10.1371/journal.pone.0095087
|View full text |Cite
|
Sign up to set email alerts
|

The CCAAT/Enhancer-Binding Protein Beta-2 Isoform (CEBPβ-2) Upregulates Galectin-7 Expression in Human Breast Cancer Cells

Abstract: Galectin-7 is considered a gene under the control of p53. However, elevated expression of galectin-7 has been reported in several forms of cancer harboring an inactive p53 pathway. This is especially true for breast cancer where galectin-7 expression is readily expressed in a high proportion in basal-like breast cancer tissues, conferring cancer cells with increased resistance to cell death and metastatic properties. These observations suggest that other transcription factors are capable of inducing galectin-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…This study identified faint EGFR immunoreactivity, scattered C/EBPβ immunoreactivity and sporadic miR-31 staining in non-cancerous oral mucosa, which is in agreement with our previous studies as well as those of others [1], [9], [33]. Since EGFR and miR-31 are highly expressed in OSCC tissues [2], [9], [10], in this study we were able to further clarify that there is concordance in the expression of EGFR, C/EBPβ and miR-31 in OSCC samples.…”
Section: Discussionsupporting
confidence: 93%
“…This study identified faint EGFR immunoreactivity, scattered C/EBPβ immunoreactivity and sporadic miR-31 staining in non-cancerous oral mucosa, which is in agreement with our previous studies as well as those of others [1], [9], [33]. Since EGFR and miR-31 are highly expressed in OSCC tissues [2], [9], [10], in this study we were able to further clarify that there is concordance in the expression of EGFR, C/EBPβ and miR-31 in OSCC samples.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, the biological role of galectin-7 cannot be solely related to its pro-apoptotic functions due to the crosstalk between both p53 and NF-jB, as recently demonstrated in MCF7 breast cancer cells [65]. In addition, recent studies have revealed that the upregulation of galectin-7 in breast cancer cell lines MCF7 and MDA-MB-231 is driven by C/EBPb-2, which can explain the paradox of concomitant galectin-7 overexpression in cancer cells and p53 mutation [66]. It should be noted that the role of C/EBP transcription factors in cellular responses to stresses, including inflammatory and ER stresses, is well known [67].…”
Section: Galectin-7mentioning
confidence: 87%
“…Understanding the molecular mechanisms controling expression of gal-14 will also be needed to determine which pathways controls its expression in specific tumor subtypes. It is interesting to note that the promoter of lgals14 contains consensus sites for both Nf-kB, Sp-1, and c/EBP, all of which have previoulsy been shown to control expression of gal-7 in cancer cells [33,40].…”
Section: Discussionmentioning
confidence: 99%